Osebno Politicno : Mednarodna fotografska razstava. - Grzinic, Marina; Cankarjev Dom, Ljublijana (Ljubljana : Cankarjev dom, 2001)
Dekleva, Luka ; Delimar, Vlasta ; Duric, Uros ; Eclipse ; Furuya, Seiichi ; Jerman, Zeljko ; Ostojic, Tanja ; Potrc, Marjetica ; Simcic, Zvonka ; Stojko, Tone ; Vajd, Aleksandra
Cankarjev dom, Ljubljana, 12. december 2001 - 13. januar 2002
kunstcatalogus